2021
DOI: 10.1111/cas.14971
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of signal regulatory protein alpha (SIRPα) expression in esophageal squamous cell carcinoma

Abstract: Signal regulatory protein alpha (SIRPα) is a type I transmembrane protein that inhibits macrophage phagocytosis of tumor cells upon interaction with CD47, and the CD47‐SIRPα pathway acts as an immune checkpoint factor in cancers. This study aims to clarify the clinical significance of SIRPα expression in esophageal squamous cell carcinoma (ESCC). First, we assessed SIRPα expression using RNA sequencing data of 95 ESCC tissues from The Cancer Genome Atlas (TCGA) and immunohistochemical analytic data from our co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…A study conducted by Kaur et al showed that breast cancer cells prevented phagocytosis by macrophages through inducing SIRPA inhibitory signaling and overexpressing CD47 protein [ 10 ]. In Koga et al's cohort, SIRP α protein was overexpressed in esophageal squamous cell carcinoma patients and predicted poor survival [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted by Kaur et al showed that breast cancer cells prevented phagocytosis by macrophages through inducing SIRPA inhibitory signaling and overexpressing CD47 protein [ 10 ]. In Koga et al's cohort, SIRP α protein was overexpressed in esophageal squamous cell carcinoma patients and predicted poor survival [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, high pre-treatment levels of sSIRPα could potentially signal a poor prognosis reflecting sSIRPα constitutively released by high numbers of TAMs. This is supported by SIRPα being constitutively released by MDMs and by recent evidence linking high SIRPα expression to poor survival in sev-eral tumors [11,[21][22][23][24]. Secondly, a rise in sSIRPα levels after initiation of immunotherapy may reflect the level of immune activation achieved, and thus predict the successfulness of the treatment.…”
Section: Discussionmentioning
confidence: 89%
“…In this work, we show that SIRPα is present as a stable soluble protein in human blood which we denote sSIRPα. A soluble form of SIRPα has previously been detected in vitro [ 11 , 13 , 14 ], but to our knowledge, this is the first time sSIRPα has been detected in the human circulation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Contradictory results have been reported in lymphomas [ 14 , 15 ]. A recent study in esophageal cancer showed that SIRPα was directly linked with invasive disease and poor prognosis [ 16 ]. In colorectal cancer high CD47 expression was linked with poor prognosis, whilst the high presence of SIRPα macrophages was linked with a favorable outcome [ 17 ].…”
Section: Introductionmentioning
confidence: 99%